Intervenção e inovação social : a interação entre técnicos e moradores de ocupação - Adilson Ramos da Silva (2021)
The partnership between social actors of diverse social origins and status, activists, technicians, advisers, researchers and social movements interweave moments of authentic encounters, but also disagreements that are still difficult to understand. How can actors in different social positions and interests find themselves in a single movement? How can militants and technicians say in a joint effort that they are there to do science or develop alternative technologies while manually helping residents of an occupation with manual tasks? How can residents of an occupation understand that militants and technicians are there to do science if the residents 'need is not to do science and residents see militants as members of a charity and do not trust the technicians' proposals? Is it possible to establish a secure base of communication between these actors so that militants and technicians are not seen as a mere charity? To answer these questions, methodological principles of Action Research were based. Technicians were interviewed, residents of the street where the joint efforts were carried out for the channeling and treatment of water and residents of other streets who participated in these joint efforts. Video recording of residents and technicians working on the construction of rainwater drainage channels was carried out. With some of them, a selfconfrontation interview was conducted based on records of observations and video recordings. Divergent actions were identified between technicians and residents, not always expressed during the joint efforts, but manifested in inaction and even undoing what had been done after the joint effort. With the intention of reflecting on these findings, it was based on previous works that describe who the individuals living in occupations are and their motivations to participate in collective actions; who are the technical individuals of higher education institutions and what is the role of the university in relation to social movements. It is observed that the form of organization of the universities and the strategies of the militants and technicians in the organization of the actions in the Occupation contributed to reduce the participation of the residents in the joint efforts.